The benefits of trusting trust: the case of Italian Soka Gakkai - Pezzi, Maria Giulia (Revista Ciências da Religião - História e Sociedade, 2014)
The article looks at the analysis of trust issues among Italian members of Japanese sect Soka Gakkai from an anthropological perspective. Trust among affiliates and neophytes can be considered as a core issue, since they do interact on a daily basis in a informal environment, with a high degree of intimacy and familiarity, and is seen as composed by an instrumental, a moral and an emotional element. This paper deals with how these components influence the lives of Soka Gakkai devotees in terms of their relationship with the religious experience, with the whole organization, with the fellow members and with themselves, starting from the assumption that analyzing the different levels of trust within a religious movement can help outlining the main elements of its ethos and the ways in which complexity is reduced.